(3GdJMQjQ aj TQM GdLGeY GdcHjQ ddTjHGfis - (3LeGd GdOjf eMehO Hf CMeO GdHNGQj GdeYQha HGdMUjQis; (3CHh YHO Gddg eMeO Hf GdMSf Hf aQbO, GdTjHGfj,J (B189 (3g` s
(3ChdgG (B:s
(3jHJOi HGdcdGe Ydi eG bHd HGH GdTgGOGJ heG jLhR efgG heG jHWd s
(3BNQgG (B:s
(3jfJgi Edi HGH eG jhLHg GdQLd Ydi faSg s
(3GdfSNI HgG MhGTs
(3ef GdfSNI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdabg GdMfajs